Developing Teaching Material in Natural Science Subject Using Inductive Thinking Models to Improve Critical Thinking of 4th Grade Students - Kosmita, Sri; Sukarno, Sukarno; Salamah, Salamah (UIN Fatmawati Sukarno Bengkulu, 2020)
There are lack of science student worksheet based on inductive thinking in the education system are. So the purpose of this study is to create appropriate and good student worksheet teaching material using inductive thinking model in science learning, and to test whether there are differences in students' critical thinking by using science teaching materials based on inductive thinking model compared to conventional teaching materials in SDN 66 Kota Bengkulu. This type of research is R&D (Research and Developmet), which was developed using the Borg and Gall model proposed by Sugiyono. The instruments in this study werequestionnaire and essay test. The data analysis technique used is the